2001
DOI: 10.1074/jbc.m008215200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Functional Characterization of a Family of Rat Brain T-type Calcium Channels

Abstract: Voltage-gated calcium channels represent a heterogenous family of calcium-selective channels that can be distinguished by their molecular, electrophysiological, and pharmacological characteristics. We report here the molecular cloning and functional expression of three members of the low voltage-activated calcium channel family from rat brain (␣ 1G , ␣ 1H , and ␣ 1I ). Northern blot and reverse transcriptase-polymerase chain reaction analyses show ␣ 1G , ␣ 1H , and ␣ 1I to be expressed throughout the newborn a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
226
1
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(240 citation statements)
references
References 58 publications
11
226
1
2
Order By: Relevance
“…As shown in Fig. 1B, a probe specific for the ␣ 1H subunit hybridized to a single ϳ8.5-kb transcript in PC12 cells, which was also detected in rat brain as previously reported (30). A second less abundant band of ϳ10 kb, detected in rat brain, was not present in PC12 cells.…”
Section: Identification Of T-type Ca 2ϩ Channels In Pc12 Cells-pc12mentioning
confidence: 60%
See 1 more Smart Citation
“…As shown in Fig. 1B, a probe specific for the ␣ 1H subunit hybridized to a single ϳ8.5-kb transcript in PC12 cells, which was also detected in rat brain as previously reported (30). A second less abundant band of ϳ10 kb, detected in rat brain, was not present in PC12 cells.…”
Section: Identification Of T-type Ca 2ϩ Channels In Pc12 Cells-pc12mentioning
confidence: 60%
“…To our knowledge, T-type Ca 2ϩ channels have not previously been reported in quiescent PC12 cells. We first tested for the presence of mRNAs coding for T-type Ca 2ϩ channel genes by performing reverse transcriptase-PCR experiments using oligonucleotides specific for each of the three previously identified T-type Ca 2ϩ channel isoforms (␣ 1G , ␣ 1H , and ␣ 1I ) (30). Fig.…”
Section: Identification Of T-type Ca 2ϩ Channels In Pc12 Cells-pc12mentioning
confidence: 99%
“…Accordingly, in the present study we measured Ba 2+ currents which were found to be identical to the currents measured when Ca 2+ was used (data not shown). These results allow us to suggest that GH3 cells may not express the α1H isoform, which has been shown to conduct Ba 2+ better than Ca 2+ (10).…”
Section: Discussionmentioning
confidence: 77%
“…The rate of deactivation was measured as the rate of decay of the tail currents at different repolarizing membrane potentials ( Figure 4 and Table 1). Somewhat surprisingly, the tail currents were best fitted by a double exponential, an unexpected finding since deactivation kinetics described for Ttype Ca 2+ current should follow a monoexponential decay (10). However, there are recent reports suggesting that CaV3.3 (α1I) channels close in a biexponential manner (15)(16)(17).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation